Not your usual suspect : older offenders of violence and abuse - Bows, Hannah (Feminist developments in violence and abuse, 2023)
As the average life expectancy continues to rise, the long-held assumption that age is a protective factor against criminal offending and victimisation is being challenged. Recognising that people who commit offences later in life are an overlooked group in criminology, Not Your Usual Suspect is the first collection to assemble research on different forms of violence and abuse perpetrated by individuals predominantly over 60. Examining intersections of gender, crime and age, this collection highlights how the increase in older people entering the criminal justice system has emphasised the unpreparedness of policies and practices for dealing with this cohort. Moving beyond existing research and policy which has focused primarily on those who are sentenced in later life for crimes they committed as younger adults - so called historic crimes - the chapters pay crucial attention to those who commit offences as long-term, repeat or first-time offenders in later life. Offering an important contribution for researchers across the criminological, gerontological, feminist and elder abuse fields, Not Your Usual Suspect expands existing research to consider the behaviour and drivers of older offenders, addressing the increasingly important issue of how the needs of this group can be addressed by policy and practice.